2011
DOI: 10.1590/s0102-05362011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of potato cultivars using SSR markers

Abstract: The potato crop has a very narrow genetic base, so the use of molecular markers is a very important tool in the characterization of germplasm banks and evaluation of genetic divergence. The objective of this study was to identify, using microsatellite or simple sequence repeat (SSR) markers, 38 accessions of potato from two collections of commercial cultivars. For the molecular characterization 10 loci were used, generating a total of 46 alleles, which were analyzed as binary data. A cluster analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
3
4
0
2
Order By: Relevance
“…In total, 44 unique alleles were detected for the 10 different loci, and the number of alleles per locus ranged from two for STPoAc58 to six for STM0030 and STM0037, with an average of 4.4 (Table ). This average number of alleles per locus was similar to those reported by Namugga, Sibiya, Melis, and Barekye () (avg = 3.9), Favoretto, Veasey, and Melo () (avg = 4.6) and Bali et al. () (avg = 4.6), but lower than in Fu et al.…”
Section: Resultssupporting
confidence: 89%
“…In total, 44 unique alleles were detected for the 10 different loci, and the number of alleles per locus ranged from two for STPoAc58 to six for STM0030 and STM0037, with an average of 4.4 (Table ). This average number of alleles per locus was similar to those reported by Namugga, Sibiya, Melis, and Barekye () (avg = 3.9), Favoretto, Veasey, and Melo () (avg = 4.6) and Bali et al. () (avg = 4.6), but lower than in Fu et al.…”
Section: Resultssupporting
confidence: 89%
“…Such an H value has been shown to be appropriate for the differentiation of various species, either propagated vegetatively or through self-pollinating, as indicated by other authors (Favoretto et al 2011;Gong & Deng 2012;Wang et al 2013). Thus, we concluded that our set of markers generated a sufficient number of data-points to allow for an unambiguous distinction of the analysed cultivars.…”
Section: Resultssupporting
confidence: 70%
“…The value is comparable to that (0.62) obtained by Smith et al (1997) for wheat SSRs. Moreover, such an H value was shown to be appropriate for the differentiation of various species, either vegetatively propagated or self-pollinating, as indicated by other authors (Favoretto et al 2011;Gong & Deng 2012;Wang et al 2013). Thus, we concluded that our set of markers generated a sufficient number of data points to allow for an unambiguous distinction of the analysed varieties.…”
Section: Resultssupporting
confidence: 74%